Analysis of Digital Service Business Development at Pln Using Swot Analysis and Business Model Canvas (BMC) (Case Study of PT PLN (Persero) UIW Nusa Tenggara Timur) - Ni Wayan Asri Vitaloka; Mohammad Riza Sutjipto (Journal Research of Social Science, Economics, and Management, 2025)
PLN’s digital transformation has advanced significantly through the implementation of digital services as a one-stop platform aimed at improving customer satisfaction and increasing company revenue. These services offer various conveniences, including bill payments, electricity token purchases, product requests, and access to a marketplace. Understanding PLN’s digital service business model is essential to support business development and service enhancement. This study analyzes PLN Mobile’s business model across customer segments based on tariff classifications using SWOT analysis and the Business Model Canvas (BMC). Additionally, external business factors are examined through PESTEL and Porter’s Five Forces frameworks to identify opportunities and threats. The research adopts a qualitative and descriptive approach, utilizing both primary and secondary data. Primary data are collected through in-depth interviews with internal and external PLN sources, while secondary data include the number of users, token purchases, complaint transactions, and PLN product requests obtained from PLN UIW NTT’s internal reports. The findings reveal that PLN’s digital services strengthen customer engagement and operational efficiency but also face challenges from technological, regulatory, and competitive dynamics. The analysis identifies 18 new strategic recommendations within a revised BMC framework, focusing on expanding customer segments, diversifying revenue streams, supporting green energy initiatives, and optimizing digital infrastructure and resources. These strategies are expected to enhance PLN’s digital service performance, improve customer experience, and contribute to sustainable growth in the national electricity sector.